2016
DOI: 10.1055/s-0042-100731
|View full text |Cite
|
Sign up to set email alerts
|

Mindestmengen und Krankenhaussterblichkeit – Beobachtungsstudie mit deutschlandweiten Krankenhausabrechnungsdaten von 2006 bis 2013

Abstract: In order to improve hospital care, minimum caseload requirements for certain elective hospital treatments have been defined by law in Germany. This study analyses retrospectively if adherence to this regulation is associated with the outcome of hospital treatment. Differences in in-hospital mortality were analyzed for complex esophageal and pancreatic surgery, liver and kidney transplantation, stem cell transplantation and total knee replacement. Within individual inpatient data of the nationwide German hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 28 publications
2
15
0
4
Order By: Relevance
“…An analysis of German hospital discharge data from 2006 to 2011 also revealed that a large proportion of hospitals perform pancreatic surgeries without achieving minimum caseload requirements and that a substantial number of pancreatic surgery inpatients was treated in such facilities [12]. This study found a mild trend towards a concentration of care structures within the field of pancreatic surgery from 2005 through 2011 (percentage of hospitals with caseload below minimum caseload requirements: 64.1 to 48.7%; percentage of pancreatic surgery cases in hospitals below minimum caseload requirements: 19.4 to 11.4%, respectively), which seemed to stop between 2011 and 2013 [9]. Another study assessed volume-outcome relationships related to pancreatic surgery using hospital discharge data from Germany's largest provider of statutory health insurance [13].…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…An analysis of German hospital discharge data from 2006 to 2011 also revealed that a large proportion of hospitals perform pancreatic surgeries without achieving minimum caseload requirements and that a substantial number of pancreatic surgery inpatients was treated in such facilities [12]. This study found a mild trend towards a concentration of care structures within the field of pancreatic surgery from 2005 through 2011 (percentage of hospitals with caseload below minimum caseload requirements: 64.1 to 48.7%; percentage of pancreatic surgery cases in hospitals below minimum caseload requirements: 19.4 to 11.4%, respectively), which seemed to stop between 2011 and 2013 [9]. Another study assessed volume-outcome relationships related to pancreatic surgery using hospital discharge data from Germany's largest provider of statutory health insurance [13].…”
Section: Resultsmentioning
confidence: 91%
“…After screening of titles and abstracts, 51 articles were excluded and of the remaining 6, 4 publications were suitable for inclusion in the present study [9,[11][12][13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experience in Germany is not much different [1,19]. Through such analyses, reliable knowledge can also be acquired for health and distribution policy discussions.…”
Section: Surgical Oncologymentioning
confidence: 99%
“…Many hospitals still fail to meet these targets and still maintain their patient care offer in this area. However, mortality in hospitals that do not comply with the Mm-R is clearly higher; a strict implementation of the Mm-R and a further specialization of hospitals for certain elective interventions could clearly improve quality of care with fewer complications and deaths [1,2]. The question posed in the title would therefore be clearly rejected.…”
Section: Introductionmentioning
confidence: 99%